The role of apoptosis in cisplatin-induced ototoxicity in rats - Freitas,Marcos Rabelo De (2009)
Cisplatin is a chemotherapy agent frequently used to treat different types of neoplasia. Ototoxicity is one of the side-effects which cause significant morbidity and limits its use. This study aimed at assessing the role of apoptosis in cisplatin-induced ototoxicity. DESIGN: experimental study. MATERIALS AND METHODS: male Wistar rats were treated with intraperitoneal cisplatin, in the doses of 24 and 16 mg/kg. The animals were assessed by means of distortion product evoked otoacoustic emissions (DPEOAE) or brainstem evoked auditory potentials (BEAP) in the third (D3) and fourth (D4) days after drug infusion onset. Following that, their cochleas were removed for immunohistochemical studies of apoptosis - TUNEL method. RESULTS: the group treated with 24 mg/kg showed a significant reduction in DPEOAE amplitude, and such fact was not seen with the 16 mg/kg. Both doses caused an increase in BEAP electrophysiological threshold in D3 and D4. Apoptosis was the injury mechanism responsible for the cisplatin-induced ototoxicity - 16 mg/kg dose, when the animals were assessed on D3. CONCLUSION: apoptosis may be involved in the cisplatin-induced ototoxicity, depending on the dose and time of injury assessment.